India another millennium (New Delhi, 2000)
In this collection of essays, fourteen of India's foremost scholars and specialists in various fields explore the challenges that lie before twenty-first century India in its quest for a democratic and just society. The volume includes essays by Bina Agarwal, Javeed Alam, Kaushik Basu, rustom Bharucha, Dipankar Gupta, Gopal Guru, Sunil Khilnani, Krishna Kumar, N.R. Narayana Murthy, Prabhat Patnaik, Dhruv Raina, N. Ram, Mahesh Rangarajan and P. Sainath.
Keywords: India-History